-2m - 5 m - 8 = 3 + (-7) + m

-2m - 5m - 8 = 3 + (-7) + m; -2m - 5m - 8 = 3 - 7 + m -2m - 5m - m = 3 - 7 + 8; -8m = 4; m = -4/8; m = -1/2

Question

Asked 5/13/2011 10:31:07 AM

Updated 8/6/2014 7:39:38 AM

1 Answer/Comment

s

Rating

8

-2m - 5m - 8 = 3 + (-7) + m;

-2m - 5m - 8 = 3 - 7 + m

-2m - 5m - m = 3 - 7 + 8;

-8m = 4;

m = -4/8;

m = -1/2

-2m - 5m - 8 = 3 - 7 + m

-2m - 5m - m = 3 - 7 + 8;

-8m = 4;

m = -4/8;

m = -1/2

Added 8/6/2014 7:39:38 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [8/6/2014 7:41:20 AM]

3(x + 2) + 4(x - 5) = 10

Question

Updated 6/16/2014 12:06:18 PM

1 Answer/Comment

3(x + 2) + 4(x - 5) = 10;

(3x + 6) + (4x - 20) = 10;

7x - 14 = 10;

7x = 10 + 14;

7x = 24;

x = 24/7

(3x + 6) + (4x - 20) = 10;

7x - 14 = 10;

7x = 10 + 14;

7x = 24;

x = 24/7

Added 6/16/2014 12:06:17 PM

This answer has been confirmed as correct and helpful.

34,465,796

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 809 [Total 6682] Ratings 19 Comments 619 Invitations 0 Offline

There are no comments.